Technological and probiotic potential of BGRA43 a natural isolate of Lactobacillus helveticus - Strahinic, Ivana; Lozo, Jelena; Terzic-Vidojevic, Amarela; Fira, Djordje; Kojic, Milan; Golic, Natasa; Begovic, Jelena; Topisirovic, Ljubisa (Frontiers in Microbiology, 2013)
Lactobacillus helveticus BGRA43 is a human intestinal isolate showing antimicrobial activity, amongst others, against Yersinia enterocolitica, Shigella sonnei, S. flexneri and Streptococcus pneumoniae. BGRA43 produces PrtH proteinase with proteolytic activity on both casein and β-lactoglobulin (BLG). BGRA43 is able to reduce the allergenicity of BLG. Bioactive peptides released in BGRA43 fermented milk are potent modulators of innate immunity by modulating the production of proinflammatory cytokines IL-6 and TNF-α. BGRA43 is able to survive in simulated gastric and intestinal conditions. The growth of BGRA43 in milk results in a fast acidification lowering the milk pH to 4.53 generating mild, homogeneous and viscous yoghurt-like product. The strain BGRA43 grows suitably in pure cow or goat’s milk as well as in milk containing inulin or nutrim even when they are used as the sole carbon source. It is suggested that strain BGRA43 could be used as a single-strain culture for the preparation of yoghurt-like products from bovine or caprine milk. Overall, L. helveticus BGRA43 could be considered as a potential probiotic candidate with appropriate technological properties attractive for the dairy industry.